X^2 + y^2 - 2x + 7y + 1 = 0
(x^2 - 2x) + (y^2 + 7y) + 1 = 0
(x^2 - 2x + 1) + (y^2 + 7y) + 1 = 0+1
(x^2 - 2x + 1) + (y^2 + 7y + 49/4) + 1 = 0+1+49/4
(x - 1)^2 + (y + 7/2)^2 + 1 = 0+1+49/4
(x - 1)^2 + (y + 7/2)^2 + 1-1 = 0+1+49/4-1
(x - 1)^2 + (y + 7/2)^2 = 49/4
(x - 1)^2 + (y + 7/2)^2 = (7/2)^2
The final answer is choice B
Answer:
You will need to use simultaneous equations.
Method:
First we need to make one set of variable the same, in this case we will:
-Multiply the top equation by 3 to get 6x
-Multiply the bottom equation by 2 to get 6x
The result will be as follows:
1) 2x+5y=-13 x3
1) 6x+15y=-39
2) 3x-4y=-8 x2
2) 6x-8y=-16
Now we will make both equations equal to 6x:
1) 6x=-15y-39
2) 6x=8y-16
Now because they both equal 6x, they therefore equal each other:
-15y-39=8y-16
-23=23y
y=-1
Now that we have y, we can substitute it back into one of the equations to get x:
1) 2x+5(-1)=-13
2x-5=-13
2x=-8
x=-4
Answer:
1/2
Step-by-step explanation:
if you want me to explain it Just tell me and i will edit it